2006
DOI: 10.1124/jpet.105.094854
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin, Modified to Not Stimulate Red Blood Cell Production, Retains Its Cardioprotective Properties

Abstract: Erythropoietin (EPO), a hematopoietic cytokine, possesses strong antiapoptotic, tissue-protective properties. For clinical applications, it is desirable to separate the hematopoietic and tissue-protective properties. Recently introduced carbamylated erythropoietin (CEPO) does not stimulate the erythropoiesis but retains the antiapoptotic and neuroprotective effects. We tested the ability of CEPO to protect cardiac tissue from toxininduced and oxidative stress in vitro and ischemic damage in vivo and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 30 publications
5
67
0
3
Order By: Relevance
“…The possibility of separating the erythropoietic and tissue protective effects of EPO could be explained through interaction with different receptors in the bone marrow and in "peripheral" tissues. Two independent studies have demonstrated that these non-erythropoietic EPO's retain their acute cardioprotective potential [31,32]. It is however uncertain whether these new EPO's will also improve cardiac function in CHF.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of separating the erythropoietic and tissue protective effects of EPO could be explained through interaction with different receptors in the bone marrow and in "peripheral" tissues. Two independent studies have demonstrated that these non-erythropoietic EPO's retain their acute cardioprotective potential [31,32]. It is however uncertain whether these new EPO's will also improve cardiac function in CHF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently introduced, carbamylated erythropoietin (CEPO) does not stimulate erythropoiesis but retains the antiapoptotic and neuroprotective effects of EPO. 71,72 Treatment with CEPO 24 hours after stroke reduces perifocal microglial activation and white matter damage, and significantly improves functional outcome after stroke. 73 Mechanisms of EPO-induced neurorestoration.…”
Section: Erythropoietinmentioning
confidence: 99%
“…EPO administration in patients also can significantly increase plasma levels of EPO well above this range of 1.0 ng/ml that has been associated with potential EPO cellular protection in patients with cardiac or renal disease (Mason-Garcia, et al, 1990, Namiuchi, et al, 2005, suggesting that the effects of EPO observed during in vitro studies may parallel the cellular processes altered by EPO in patients with DM (Bierer, et al, 2006). Furthermore, EPO can block apoptotic DNA degradation in ECs during elevated glucose similar to other models of oxidative stress in cardiac and vascular cell models (Avasarala and Konduru, 2005, Chong, et al, 2002b, Moon, et al, 2006. The preservation of cellular energy reserves is dependent upon the maintenance of mitochondrial integrity during DM (Newsholme, et al, 2007).…”
mentioning
confidence: 93%